EFEKTIFITAS OPERASI SC ERACS TERHADAP MOBILISASI PASIEN DAN LAMA PERAWATAN: EFEKTIFITAS OPERASI SC ERACS TERHADAP MOBILISASI PASIEN DAN LAMA PERAWATAN - Rudiantoro, Danar; Wardani, Ratna (LPPM STIKes Bahrul Ulum Jombang, 2024)
Background: Sectio Caesarea is a birth operation that has been proven to reduce maternal mortality when vaginal delivery is indicated to be risky. Wound healing in Sectio Caesarea surgery patients requires good blood circulation for cell growth or repair. Mobilization will improve blood circulation and you may soon experience recovery or healing. Method: A literature search was carried out based on articles published between 2018-2023 according to the inclusion and exclusion criteria that had been determined using 1 data base, namely Google Schoolar. This literature search uses the PRISMA guideline in carrying out the screening process. From the search results, 200 articles were obtained. After carrying out the screening process, there were 8 articles that met the criteria and will be analyzed. Results: Based on a review of 8 literature, it was found that SC ERACS was effective in speeding up patient mobilization and shortening the length of treatment Conclusion: From the results of a literature review of 8 journals, it was found that SC ERACS was effective in speeding up patient mobilization and shortening the length of treatment.